Comparative genomics of non-pseudomonal bacterial species colonising paediatric cystic fibrosis patients - Ormerod, Kate L.; George, Narelle M.; Fraser, James A.; Wainwright, Claire; Hugenholtz, Philip (PeerJ, 2015)
The genetic disorder cystic fibrosis is a life-limiting condition affecting ∼70,000 people worldwide. Targeted, early, treatment of the dominant infecting species, Pseudomonas aeruginosa, has improved patient outcomes; however, there is concern that other species are now stepping in to take its place. In addition, the necessarily long-term antibiotic therapy received by these patients may be providing a suitable environment for the emergence of antibiotic resistance. To investigate these issues, we employed whole-genome sequencing of 28 non-Pseudomonas bacterial strains isolated from three paediatric patients. We did not find any trend of increasing antibiotic resistance (either by mutation or lateral gene transfer) in these isolates in comparison with other examples of the same species. In addition, each isolate contained a virulence gene repertoire that was similar to other examples of the relevant species. These results support the impaired clearance of the CF lung not demanding extensive virulence for survival in this habitat. By analysing serial isolates of the same species we uncovered several examples of strain persistence. The same strain of Staphylococcus aureus persisted for nearly a year, despite administration of antibiotics to which it was shown to be sensitive. This is consistent with previous studies showing antibiotic therapy to be inadequate in cystic fibrosis patients, which may also explain the lack of increasing antibiotic resistance over time. Serial isolates of two naturally multi-drug resistant organisms, Achromobacter xylosoxidans and Stenotrophomonas maltophilia, revealed that while all S. maltophilia strains were unique, A. xylosoxidans persisted for nearly five years, making this a species of particular concern. The data generated by this study will assist in developing an understanding of the non-Pseudomonas species associated with cystic fibrosis.
Keywords: Comparative genomics; Cystic fibrosis; Microevolution; Antibiotic resistance; Lateral gene transfer; Host adaptation; Serial isolates